In‐chain neutral hydrocarbon loss from crocin apocarotenoid ester glycosides and the crocetin aglycon (Crocus sativus L.) by ESI‐MSn (n = 2, 3). (4th December 2013) - Pittenauer, Ernst; Koulakiotis, Nikolaos Stavros; Tsarbopoulos, Anthony; Allmaier, Guenter
<x xml:space="preserve">Abstract</x> The stigmas of Crocus sativus L. have been used as spice and colorant agent (i.e. saffron) for more than 4000 years. For an updated structural investigation of the aglycon present in the glycosylated crocetin apocarotenoids (i.e. crocins), seven representative derivatives ranging from one up to five glucosyl‐residues with a maximum number of three monosaccharides per glycosylation site (glucose, gentiobiose, gentiotriose and neapolitanose) were isolated and purified by high‐performance liquid chromatography. The compounds selected for further mass spectrometric investigation include glucosyl‐, bis‐glucosyl‐, gentiobiosyl‐, gentiobiosyl‐glucosyl‐, bis‐gentiobiosyl‐, gentiobiosyl‐gentiotriosyl‐ and gentiobiosyl‐neapolitanosyl‐crocetin. Electrospray ionization in combination with low‐energy collision‐induced dissociation/tandem mass spectrometry of sodiated crocin precursor ions utilizing either a 3D‐ion trap (MSn, n = 2, 3) or a QqTOF instrument, with the latter providing accurate mass determination with an accuracy of ±1–3 ppm or better at a resolution of 10 000 (full width at half maximum), was used. Major fragmentation pathways included loss of either one or two carbohydrate substituents leading to the sodiated aglycon without interglycosidic bond cleavage during in MS2‐experiments. All sodiated precursor ions and major product ions were accompanied by a loss of 92 Da, which was elucidated as C7H8‐loss from the aglycon by skeletal rearrangement via an eight‐membered transition state as previously described for intact C40‐carotenoids. Copyright © 2013 John Wiley & Sons, Ltd.